Bacterial and Antibiogram Profile of Urinary Tract Infection Patients in a Tertiary Hospital, Surabaya, Indonesia - Utami, Mahrumi Dewi Tri; Wahyunitisari, Manik Retno; Mardiana, Nunuk; Setiabudi, Rebekah Juniati (Folia Medica Indonesiana, 2022)
Highlights: • Most urinary tract infections are caused by Gram-negative bacteria with E. coli being the most common bacteria. • Antibiotics with the highest susceptibility for Gram-negative bacteria were ertapenem, meropenem, amikacin, and imipenem. • Antibiotics with the highest susceptibility for Gram-positive bacteria mainly were susceptible to chloramphenicol,streptomycin, vancomycin, rifampin, tigecycline, teicoplanin, and ampicillin. Abstract: Urinary tract infection (UTI) is one of the most common bacterial infections. Inappropriate antibiotic use for UTI treatment may lead to antibiotic resistance. This study aimed to provide an updated bacterial and antibiogram profile from urine specimens of patients diagnosed with UTI. This study was a retrospective study using urine culture and antibiotic susceptibility test results obtained from Clinical Microbiology Laboratory in a tertiary general hospital in Surabaya, Indonesia for a two-month period patients. Most aged more than and/or equal to 59 years, in both sexes. Gram-negative bacteria, particularly , was being the most between June to July 2019. There were 215 patients with significant urine culture results of 54.4% from Escherichia coli female bacteria were carbapenem antibiotics and amikacin, while teicoplanin and vancomycin were some antibiotics susceptible to gramcommon bacteria that caused UTI, followed by K. pneumoniae. Some antibiotics with the highest susceptibility to gram-negative positive bacteria. This study result indicated that there was an urge to conduct local antibiogram profile investigation due to the low susceptibilities shown in recent empirical therapy recommendations, such as trimethoprim sulfamethoxazole, fluoroquinolone, nitrofurantoin, and fosfomycin.